Seorang Perempuan Berusia 10 Tahun dengan Takikardia Supraventrikular (Diduga AVNRT/AVRT) dan Hemodinamik Stabil: Laporan Kasus - Miranti Kemala Suri; Andi Alief; Yulius Patimang (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Supraventricular tachycardia (SVT) is one of the most common arrhythmias in the pediatric population, often resulting from re-entry mechanisms involving accessory pathways or dual atrioventricular nodal physiology. Although generally well tolerated in children with structurally normal hearts, its management can be challenging, particularly in recurrent or persistent cases. This study is a case report describing a pediatric patient with hemodynamically stable SVT treated at Dr. Wahidin Sudirohusodo Hospital. Data were collected retrospectively from medical records, including history taking, physical examination, and supporting investigations such as serial electrocardiography (ECG), laboratory tests, chest radiography, and transthoracic echocardiography. Management was conducted according to current clinical guidelines, including vagal maneuvers, pharmacological therapy with beta-blockers and antiarrhythmic agents (amiodarone), and monitoring of treatment response based on clinical evaluation and ECG, along with identification and treatment of underlying triggers. We report a case of a 10-year-old female presenting with suspected SVT and pericarditis, who experienced episodes of narrow QRS complex tachycardia that were successfully converted to sinus rhythm following amiodarone administration. Echocardiographic evaluation revealed mild to moderate tricuspid regurgitation with preserved ventricular function. Laboratory and radiological findings suggested an underlying inflammatory process, which was considered a triggering factor. This case highlights the importance of a comprehensive approach in the diagnosis and management of pediatric SVT, including addressing underlying conditions and ensuring continuous monitoring to prevent recurrence.